Probabilistic finite element analysis of steel roof truss using Ansys - Khong, Jia Wei (2012)
Truss is one of the important components for a structure and need to be designed in such a way that they have enough strength and rigidity to satisfy the strength and serviceability limitation. So, truss required a proper method to be analyzes. Among all those methods, finite element analysis shall be one of the best methods in analyzing the truss because it can analyze complex structure without simplify the structure. However, during the designation of truss, there is a possibility that randomness and uncertainty may occur, thus probabilistic analysis shall be apply to solve this problem. Here, the study was conducted to prove that a steel roof truss under the existence of randomness and uncertainty can be analyzed by apply probabilistic finite element analysis using ANSYS. This report presents an alternative way in the designation of steel roof truss with many uncertainties.